146k views
0 votes
Can someone please help I really don’t understand this please explain.

Can someone please help I really don’t understand this please explain.-example-1
User Duckworthd
by
6.3k points

2 Answers

5 votes

Answer:

D

Explanation:

User NewNewton
by
5.9k points
5 votes

Answer:

The answer is option D.

Explanation:

You have to multiply it :

h(x) × g(x) = (h×g)(x)

(h×g)(x) = (x² + 2x)(-3x + 4)

(h×g)(x) = -3x³ + 4x² - 6x² + 8x

(h×g)(x) = -3x³ - 2x² + 8x

User Chris Gonzales
by
7.0k points